Pengembangan Keuangan Mikro Islam untuk Mengatasi Kemiskinan dan Mencapai Tujuan SDGs: Pendekatan Bibliometrik: Developing Islamic Microfinance to Address Poverty and Achieve SDGs: A Bibliometric Approach - Haidar, Abdullah (Universitas Darussalam Gontor, 2024)
This study tries to review research on sustainable microfinance development in Scopus indexed journals. This analysis uses descriptive statistical analysis based on 319 selected papers related to microfinance sustainable development from both national and international journals. All samples of published journals have been published for 27 years from 1996 to 2022. The data is then processed and analyzed using the VOSviewer application program to find out the bibliometric visualization map for sustainable development of microfinance research. The results of this bibliometric mapping study show a map of the development of research in the field of microfinance sustainable development. This study also found a close relationship between microfinance sustainable development and the main goal of the SDGs, namely eradicating poverty to promote prosperity for all people of all ages around the world. This research finds new and interesting keywords for further research.